Lopinavir/Ritonavir for COVID-19: a Systematic Review and Meta-Analysis - Bahman Amani; Ahmad Khanijahani; Behnam Amani; Payam Hashemi (Frontiers Media S.A., 2021)
Purpose: To provide the latest evidence on the efficacy and safety of lopinavir/ritonavir compared to other treatment options for COVID-19. Methods: We searched PubMed, Cochran Library, Embase, Scopus, and Web of Science for the relevant records up to April 2021. Moreover, we scanned MedRxiv, Google Scholar, and clinical registry databases to identify additional records. We have used the Newcastle-Ottawa Scale and Cochrane risk of bias tools to assess the quality of studies. This Meta-analysis was conducted using RevMan software (version 5.3). Results: Fourteen studies were included. No significant difference was observed between lopinavir/ritonavir and non-antiviral treatment groups in terms of negative rate of PCR (polymerase chain reaction) on day 7 (risk ratio [RR]: 0.83; 95% CI: 0.63 to 1.09; P=0.17), and day 14 (RR: 0.93; 95% CI: 0.81 to 1.05; P=0.25), PCR negative conversion time (mean difference [MD]: 1.09; 95% CI: -0.10 to 2.29; P=0.07), secondary outcomes, and adverse events (P>0.05). There was no significant difference between lopinavir/ritonavir and chloroquine as well as lopinavir/ritonavir and hydroxychloroquine regarding the efficacy outcomes (P>0.05). However, lopinavir/ritonavir showed better efficacy than arbidol for the same outcomes (P<0.05). Lopinavir/ritonavir plus arbidol was effective compared to arbidol alone in terms of the negative rate of PCR on day 7 (P=0.02). However, this difference was not significant regarding other efficacy outcomes (P>0.05). Conclusion: Lopinavir/ritonavir has no more treatment effects than other therapeutic agents used herein in COVID-19 patients.